UKURAN USAHA DAN RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Stefanny Claudya; Rudi Setiadi Tjahjono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The objective of the study is to gather empirical data on the influence of firm size and financial ratios such as profitability, capital structure, liquidity, earnings per share, investment decision, and activity ratio on the firm value. This study will make use of manufacturing companies that are listed on IDX between 2019 to the year 2021. The purposive sampling method is utilized in this study. There are 80 companies and 240 data were used in this study. Multiple regression is utilized in this study. The result demonstrates that firm size, profitability, and capital structure have an effect on firm value while liquidity, earnings per share, price-earnings ratio, and activity ratio have no effect on firm value.